(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to identify the highest activation in Vastus Medialis (VMO), Vastus Lateralis (VL) and Rectus Femoris (RF) while performing various squat exercises to create an effective exercising method. Method/Statistical Analysis: 40 healthy subjects (males 23, females 17) from S University were recruited. Subjects performed four different types of squats; General Squats (GS), Instability Squats on an unstable surface (IS), Knee Adduction Squats (KAS), and Wall squats (WS). The difference in the activation of VMO, VLO and RF were recorded during the various exercises were analyzed and recorded with the EMG. Findings: Measurements of all the experiments were analyzed using one-way ANOVA. Within these results, RF showed the most activation during (WS) and the least activation during (KAS). However, there were no significant differences found between (GS) and (IS). VLO showed the most activation during (GS). On the other hand, there were no significant differences found within (IS) and (WS). In addition to our results, VMO showed the least activation during (KAS). All three muscles displayed different activation patterns during each squat exercise. Improvements/Applications: Considering these findings, this study may help to design a more effective exercise for specific muscles when strengthening the leg muscles.